Analisis Kritis Implementasi Kurikulum Merdeka dalam Pengembangan Kompetensi Berpikir Kritis Siswa Sekolah Dasar - Muzdalifah Muzdalifah; Yantoro Yantoro; Eka Sastrawati (Lembaga Pengembangan Kinerja Dosen, 2026)
The Merdeka Curriculum represents Indonesia’s national education reform aimed at transforming learning paradigms toward a more contextual, flexible, and student-centered approach aligned with the Pancasila Student Profile. One of its key priorities is fostering critical thinking competence from the elementary level. This article aims to critically analyze the implementation of the Merdeka Curriculum in developing students’ critical thinking skills in Indonesian elementary schools. Employing a conceptual and literature-based approach, this study examines educational policies, theories of critical thinking, and recent research findings (2020–2025). The analysis reveals that the Merdeka Curriculum holds strong potential to enhance critical thinking through differentiated learning, project-based learning, authentic assessment, and the Pancasila Student Profile projects. Nevertheless, its implementation still encounters challenges, particularly regarding teacher competence, infrastructure readiness, and non-reflective learning culture. Therefore, strengthening teacher capacity, reforming assessment systems, and cultivating critical thinking as a school-wide culture are essential to realizing the goals of the Merdeka Curriculum effectively at the elementary education level.